2020
DOI: 10.1177/0021998320914366
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanical properties of composites based on nitrile butadiene rubber using graphene nanoplatelets

Abstract: This paper presents the results of a study of the strength and thermophysical properties of the composite material graphene nanoplatelets (GNP)–nitrile butadiene rubber (NBR) (GNP@NBR). High-quality GNP were massively produced by self-propagating high-temperature synthesis (SHS) method. It was found that the introduction of GNP in concentrations up to 6 wt.% leads to an increase in tensile strength up to 62%, resistance to tearing up to 64% thermal conductivity up to 2. The use of GNP allowed increasing the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…It was shown that, in terms of their morphometric parameters, the obtained 2D graphene structures belong to FLG [7]. To date, it has been shown that the obtained FLG is promising in polymer materials science [9], as a basis for radionuclides sorbent [10]. The ability to obtain FLG in product volume sufficient for real application and the shown promise of their use in a wide range of practical applications determined the choice as an object of this research FLG synthesized using the SHS process.…”
Section: Introductionmentioning
confidence: 91%
“…It was shown that, in terms of their morphometric parameters, the obtained 2D graphene structures belong to FLG [7]. To date, it has been shown that the obtained FLG is promising in polymer materials science [9], as a basis for radionuclides sorbent [10]. The ability to obtain FLG in product volume sufficient for real application and the shown promise of their use in a wide range of practical applications determined the choice as an object of this research FLG synthesized using the SHS process.…”
Section: Introductionmentioning
confidence: 91%
“…In 2020, thermophysical properties and the strength of NBR nanocomposites using high‐quality graphene nanoplatelets (GnPs) were studied. [ 57 ] GnPs were synthesized by the self‐propagating high‐temperature synthesis (SHS) method. An increase in tensile strength, thermal conductivity, and anti‐wear was achieved due to the homogeneity of the GnPs in the polymer matrix.…”
Section: Acrylonitrile‐based Polymer/graphene Nanocompositesmentioning
confidence: 99%
“…This study investigated the improved electrical conductivity properties of graphene-filled rubber nanocomposites [19] and the propagation properties of cracks in test specimens with a single edge notch. DIC technique was used to observe the crack resistance function depending on the local strain distribution.…”
Section: Introductionmentioning
confidence: 99%